Radiofluorescence as a detection tool for quartz luminescence quenching processes - Friedrich, Johannes; Kreutzer, Sebastian; Schmidt, Christoph (Radiation measurements, 2018)
Thermal quenching is a well-known phenomenon in quartz, which describes the decrease in luminescence efficiency (light output) with sample temperature. In the present work, the UV radiofluorescence (RF) signals of three different quartz samples during cooling from 500°C to room temperature were monitored and analysed. Resulting thermal quenching parameters W (activation energy) and K (constant) agree with published values, except for one sample. Another quenching process in quartz is the reduction of luminescence sensitivity following irradiation (dose quenching), mainly known for TL and OSL of old samples with large palaeodoses. Here, the intensity of the 110°C TL peak and the OSL signal were used to monitor the dose quenching effect. UV-OSL and UV-TL signals are analysed and found to be very similar. The UV-RF recorded during irradiation in between repeated cycles of TL and OSL measurements differs at high doses from a continuously recorded reference signal. Furthermore, numerical simulations are presented to decipher the charge transport processes in quartz. In summary, thermal quenching simulations are capable of mimicking experimental findings and confirm that UV-RF is a valuable tool to determine thermal quenching parameters. Dose quenching simulations differ from experimental results in the high dose range but help to understand the basic principle of dose quenching: charge competition of different centres.